Refractory tracheoesophageal fistula treated using multi-stage surgery: A case report - Nakagawa, Yoichi; Makita, Satoshi; Uchida, Hiroo; Hinoki, Akinari; Shirota, Chiyoe; Sumida, Wataru; Amano, Hizuru; Okamoto, Masamune; Takimoto, Aitaro; Ogata, Seiya; Takada, Shunya; Kato, Daiki; et al. (Frontiers in Pediatrics, 2022)
A tracheoesophageal fistula (TEF) recurs in approximately 2%–13% of cases of esophageal atresia with TEF that are treated surgically. Currently, there is no consensus on the most effective treatment to prevent recurrent TEF (RTEF). Herein, we present a patient with type C esophageal atresia who underwent thoracoscopic esophago-esophageal anastomosis and TEF repair at 2 days old. However, RTEFs were observed at ages 3, 6, and 11 months, and thoracoscopic TEF repairs using a pleural patch, fascia lata graft, and pectoralis major myocutaneous (PMMC) flap were performed, respectively. A fourth recurrence led to mediastinitis, shock liver, disseminated intravascular coagulopathy, and a compromised respiratory status. Hence, laparoscopic esophageal transection was first performed to improve the respiratory condition by preventing the regurgitation of gastric contents. Once the patient was stable, a subtotal esophageal resection with TEF closure followed by gastric tube reconstruction was performed. In conclusion, we encountered a case of refractory RTEF that was repaired four times using various techniques, including a fascia lata graft and PMMC flap. However, TEF still recurred after these four operations. The final surgical strategy involved an esophageal transection as a palliative therapy, which improved the respiratory condition, followed by closure of the TEF and subtotal esophageal resection. Finally, esophageal reconstruction using a gastric tube after the complete remission of inflammation was effective. This multi-stage surgery was considered the only choice to rescue the patient and effectively prevent another recurrence.